Methionine enkephalin (MENK) regulates the immune pathogenesis of type 2 diabetes mellitus via the IL-33/ST2 pathway - Zhang, Keying; Yang, Jing; Ao, Na; Jin, Shi; Qi, Ruiqun; Shan, Fengping; Du, Jian (International immunopharmacology, 2019)
The incidence and mortality of type 2 diabetes mellitus (T2DM) rank among the top ten worldwide. Emerging studies indicate pathological roles for the immune system in inflammation, insulin resistance and islet β-cell damage in subjects with T2DM. Methionine enkephalin (MENK) is present in endocrine cells of the pancreas and has been suggested to be an important mediator between the immune and neuroendocrine systems. Therefore, it may play a role in modulating insulin secretion from islet cells. Since little is known about the effect of MENK on T2DM, therefore it was the aim of this study to characterize the role and possible mechanism of action of MENK on plasma glucose and serum insulin levels in T2DM rats and INS-1 cells in vivo and in vitro. MENK significantly decreased the plasma glucose level and increased the serum insulin concentration in T2DM rats. It also increased the serum levels of the cytokines IL-5 and IL-10, while decreased TNF-α and IL-2 levels. We further confirmed that MENK regulated glucose metabolism by upregulating opioid receptor expression and modulating the IL-33/ST2 and MyD88-TRAF6-NF-κB p65 signaling pathways. Based on these results, an intraperitoneal injection of MENK represents a potentially new approach for T2DM. •MENK reduced glucose level and increased serum insulin level in T2DM rats.•MENK increased the expressions of opioid receptors in rat pancreas.•MENK downregulated the MyD88-TRAF6-NF-κB p65 signaling pathway in pancreas of rats.•MENK regulated serum Th1/Th2 cytokines to inhibit the secretion of inflammatory cytokines.